Design of ultrathin transparent cross‐polarization converter. Issue 1 (7th October 2022) - He, Yulian; Kou, Na; Yu, Shixing; Ding, Zhao; Zhang, Zhengping
Abstract: In this letter, we propose a novel transparent wideband reflective metasurface based on indium tin oxide (ITO) material. The unit consists of four C‐shaped structures of different sizes. ITO material was plated on the surface of soda‐calcium glass by magnetron sputtering. Floquet port and master‐slave boundary conditions were set up in ANSYS HFSS for simulation. Simulation results show that the polarization conversion ratio reaches 90% in the range of 10.9–20.5 GHz, with little change in the 30° incident angle range. Experimental results are consistent with the simulation ones. The proposed transparent cross‐polarization converter may be used in the devices integrated with solar cells.